2010
DOI: 10.1111/j.1600-0579.2009.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and tendency of cheating behaviours amongst undergraduate students in a Dental Institution of India

Abstract: Honesty and integrity are key characteristics expected of a doctor, although academic misconduct amongst medical students is not new. Academic integrity provides the foundation upon, which a flourishing academic life rests. The aim of this study was to investigate the attitude of undergraduate dental students about the seriousness of cheating behaviours and to determine the rate of malpractice amongst these students. A self designed closed ended questionnaire was distributed to 300 undergraduate students in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…They concluded with the suggestion of establishing centers for academic integrity in India. There were also other studies of medical institutions of India which highlighted academic misconduct a critical problem which needs to be deterred soon [16][17][18][19][20] . Johnson 21 , et al raised various questions on the use of bibliometrics techniques especially when online journals are the key access points for producer and user of information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded with the suggestion of establishing centers for academic integrity in India. There were also other studies of medical institutions of India which highlighted academic misconduct a critical problem which needs to be deterred soon [16][17][18][19][20] . Johnson 21 , et al raised various questions on the use of bibliometrics techniques especially when online journals are the key access points for producer and user of information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature has indicated that students justify academic dishonesty due to a "fear of failure" (Monica et al, 2010). The research indicated that there is a statistically significant correlation between the justifications of academically dishonest behaviours and the willingness to report the severe academic dishonesty.…”
Section: Discussionmentioning
confidence: 96%
“…Os dados sobre a frequência da prática de comportamentos desonestos pelos estudantes foram recolhidos através de um questionário traduzido e adaptado de um estudo de Hrabak et al [1] e onde são analisados 11 tipos de comportamentos passíveis de serem considerados como prática de desonestidade académica, classificados utilizando uma escala de Likert de 5 pontos: de 1 ('nunca') a 5 ('sempre'). Para avaliar a perceção dos estudantes sobre a gravidade daqueles comportamentos foi usado um questionário traduzido e adaptado de Monica et al [6] com uma escala de Likert de 4 níveis: de 1 ('não grave') até 4 ('muito grave').…”
Section: Materiais E Métodosunclassified